Decoration of Silver Nanoparticles on Multiwalled Carbon Nanotubes: Antibacterial Mechanism and Ultrastructural Analysis. (28th February 2015) - Dinh, Ngo Xuan; Quy, Nguyen Van; Huy, Tran Quang; Le, Anh-Tuan
Abstract : Recently, development of carbon nanocomposites composed of carbon nanostructures and metal nanoparticles has attracted much interests because of their large potential for technological applications such as catalyst, sensor, biomedicine, and disinfection. In this work, we established a simple chemistry method to synthesize multiwalled carbon nanotubes (MWCNTs) decorated with silver nanoparticles (Ag-NPs) using a modified photochemical reaction (Tollens process). The formation and interaction of Ag-NPs with functionalized groups on the surface of MWCNTs were analyzed by X-ray diffraction, transmission electron microscopy, Raman spectroscopy, and Fourier-transform infrared spectroscopy. The average size of Ag-NPs on the MWCNTs was approximately 7 nm with nearly uniform size distribution. Antibacterial effect of Ag-MWCNTs nanocomposites was evaluated against two pathogenic bacteria including Gram-negative Escherichia Coli and Gram-positive Staphylococcus aureus bacteria. Interaction and bactericidal mechanism of Ag-MWCNTs with tested bacteria was studied by adapting the electron microscopy. Analysis on ultrastructural changes of bacterial cells indicates that antibacterial action mechanism of Ag-MWCNTs is physical interaction with cell membrane, the large formation of cell-Ag-MWCNTs aggregates, and faster destructibility of cell membrane and disruption of membrane function, hence resulting in cells death.